Epigallocatechin gallate triggers apoptosis by suppressing de novo lipogenesis in colorectal carcinoma cells. Issue 5 (17th March 2022) - Khiewkamrop, Phuriwat; Surangkul, Damratsamon; Srikummool, Metawee; Richert, Lysiane; Pekthong, Dumrongsak; Parhira, Supawadee; Somran, Julintorn; Srisawang, Piyarat
Abstract : The de novo lipogenesis (DNL) pathway has been identified as a regulator of cancer progression and aggressiveness. Downregulation of key lipogenesis enzymes has been shown to activate apoptosis in cancerous cells. Epigallocatechin gallate (EGCG) inhibits cancer cell proliferation without causing cytotoxicity in healthy cells. The present study aimed to investigate the effects of EGCG on the promotion of apoptosis associated with the DNL pathway inhibition in cancer cells, both in vitro and in vivo . We observed that two colorectal cancer cell lines (HCT116 and HT‐29) had a higher cytotoxic response to EGCG treatment than hepatocellular carcinoma cells, including HepG2 and HuH‐7. EGCG treatment decreased cell viability and increased mitochondrial damage‐triggered apoptosis in both HCT116 and HT‐29 cancer cells. Additionally, we treated mice transplanted with HCT116 cells with 30 or 50 mg·kg −1 EGCG for 7 days to evaluate the apoptotic effects of EGCG treatment in a xenograft mouse model of cancer. We observed a decrease in intracellular fatty acid levels, which suggested that EGCG‐induced apoptosis was associated with a decrease in fatty acid levels in cancer. Suppression of ATP synthesis by EGCG indicated that cell death induction in cancer cells could be mediated by shared components of the DNL and energy metabolism pathways. In addition, EGCG‐induced apoptosis suppressed the expression of the phosphorylation protein kinase B and extracellular signal‐regulated kinase 1/2 signaling proteins in tumors from xenografted mice. Cytotoxic effects in unaffected organs and tissues of the mouse xenograft model were absent upon EGCG treatment. Abstract : Epigallocatechin gallate (EGCG) caused cytotoxicity and mitochondrial damage‐induced apoptosis in colorectal HCT116 cancer cells. A decrease in fatty acid levels was associated with EGCG‐induced apoptosis. Additionally, the reduction of ATP generation by EGCG revealed that components of the de novo lipogenesis and energy metabolism pathways are implicated in apoptosis. Furthermore, EGCG‐induced apoptosis reduced the expression of phosphorylated protein kinase B and extracellular signal‐regulated kinase 1/2 signaling proteins.